Pengaruh Relationship Marketing dan Eservicescape terhadap Loyalitas Pelanggan: Studi pada Pengguna E-Commerce Tokopedia di Kota Medan (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the influence of relationship marketing and e-servicescape on customer loyalty of Tokopedia users in Medan City. The rapid development of digital technology encourages Tokopedia to build long-term relationships with customers while creating a convenient and secure online shopping experience. This research employed a quantitative method with an associative approach, using data collected through questionnaires distributed to 100 Tokopedia users in Medan City and analyzed using multiple linear regression. The results show that relationship marketing has a positive and significant effect on customer loyalty, where effective communication, responsive services, and loyalty programs such as Tokopedia Points increase customer trust and emotional attachment. In addition, e-servicescape also has a positive and significant effect on customer loyalty through an attractive interface, easy navigation, and reliable transaction security. Simultaneously, both variables make a substantial contribution to building customer loyalty toward Tokopedia. Thus, effective relationship marketing strategies and high-quality digital environments are crucial factors in maintaining customer loyalty and enhancing Tokopedia’s competitiveness in the increasingly intense e-commerce industry.